Kinematical Research of Free-Floating Space-Robot System at Position Level Based on Screw Theory - Yong Wang; Xiaojun Liang; Kejie Gong; Ying Liao (International Journal of Aerospace Engineering)
Kinematics of a free-floating space-robot system is a fundamental and complex subject. Problems at the position level, however, are not considered sufficiently because of the nonholonomic property of the system. Current methods cannot handle these problems simply and efficiently. A novel and systematical modeling approach is provided; forward and inverse kinematics at the position level are deduced based on the product of exponentials (POE) formula and conservation of linear momentum. The whole deduction process is concise and clear. More importantly, inertial tensor parameters are not introduced. Then, three situations with different known variables are mainly studied. Due to the complexity of inverse kinematical equations, a numerical method is proposed based on Newton’s iteration method. Two calculation examples are given, a dual-arm planar model and a single-arm spatial model; both forward and inverse kinematical solutions are given, while inverse kinematical results are compared with simulation results of Adams. The results indicate that the proposed methods are quite accurate and efficient.